Pengaruh Gaya Kepemimpinan, Kompensasi, Motivasi, Dan Lingkungan Kerja Terhadap Peningkatan Kinerja Guru - Isnaini, Bunga Nur; Rachmawati, Eny; Cahyani, Diah; Rizkawati, Nidya (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
The aim of this research is to analyze the influence of leadership style, compensation, motivation and work environment, both partially and simultaneously on improving teacher performance at Madrasah Ibtidaiyah Miftahul Huda Sumbertanggul, Mojosari District, Mojokerto Regency. The research method used was a quantitative approach, involving the participation of 30 teachers. Data was collected through distributing questionnaires and analyzed using multiple regression. The results of the analysis show that leadership style, compensation, motivation and work environment simultaneously or partially influence teacher performance improvement at Madrasah Ibtidaiyah Miftahul Huda, Sumbertanggul, Mojosari District, Mojokerto Regency. With an adjusted R-square value of 0.766, it shows that 76.6% of the variation in teacher performance improvement can be explained by these factors and 23.4% is influenced by factors outside the scope of the research. The conclusions of this research are: 1) Leadership style has a partially significant effect on improving teacher performance. 2) Compensation has a partially significant effect on improving teacher performance. 3) Motivation has a partially significant effect on improving teacher performance. 4) The work environment has a partially significant effect on improving teacher performance. 5) Leadership Style, Compensation, Motivation and Work Environment simultaneously have a significant effect on improving teacher performance.